Supramolecularly enabled pH- triggered drug action at tumor microenvironment potentiates nanomedicine efficacy against glioblastoma. (January 2021) - Quader, Sabina; Liu, Xueying; Toh, Kazuko; Su, Yu-Lin; Maity, Amit Ranjan; Tao, Anqi; Paraiso, West Kristian D.; Mochida, Yuki; Kinoh, Hiroaki; Cabral, Horacio; Kataoka, Kazunori
Abstract: The crucial balance of stability in blood-circulation and tumor-specific delivery has been suggested as one of the challenges for effective bench-to-bedside translation of nanomedicines (NMs). Herein, we developed a supramolecularly enabled tumor-extracellular (T ex ) pH-triggered NM that can maintain the micellar structure with the entrapped-drug during systemic circulation and progressively release drug in the tumor by rightly sensing heterogeneous tumor-pH. Desacetylvinblastine hydrazide (DAVBNH), a derivative of potent anticancer drug vinblastine, was conjugated to an aliphatic ketone-functionalized poly(ethylene glycol)–b-poly(amino acid) copolymer and the hydrolytic stability of the derived hydrazone bond was efficiently tailored by exploiting the compartmentalized structure of polymer micelle. We confirmed an effective and safe therapeutic application of T ex pH-sensitive DAVBNH-loaded micelle (T ex -micelle) in orthotopic glioblastoma (GBM) models, extending median survival to 1.4 times in GBM xenograft and 2.6 times in GBM syngeneic model, compared to that of the free DAVBNH. The work presented here offers novel chemical insights into the molecular design of smart NMs correctly sensing T ex -pH via programmed functionalities. The practical engineering strategy based on a clinically relevant NM platform, and the encouraging therapeutic application of T ex -micelle in GBM, one of the most lethal human cancers, thus suggests the potential clinical translation of this system against other types of common cancers, including GBM. Graphical abstract: Image 1